SALAT DALAM TRADISI ISLAM KEJAWEN - Khalim, Samidi (Fakultas Ilmu Budaya Universitas Diponegoro, 2011)
Islam Kejawen here is meant as Islam as practiced in the Kingdom of Java. A reflection of Islam Kejawen can be seen in the works of literature written by the kingdom poets. This paper raises thoughts of Kraton Surakarta poet, Ngabehi Sastrawijaya, who lived during the reign of Paku Buwana III and Paku Buwana IV. The works of Sastrawijaya analyzed are Suluk Sajatining Salat and Suluk Salat Sarengat Tarekat Hakekat Makripat stored in the library of the Kingdom of Surakarta Museum, Museum Sasana Pustaka. This article analyzes the text to reveal both the meaning and function of the suluk for Islam Kejawen practice.